PENGARUH ENTERPRISE RISK MANAGEMENT DISCLOSURE, INTELLECTUAL CAPITAL DISCLOSURE DAN STRUKTUR PENGELOLAAN TERHADAP NILAI PERUSAHAAN - Dedi Ardianto; Muhammad Rivandi (Fakultas Ekonomi Dan Bisnis, Universitas Mercu Buana, Jakarta, 2018)
This study aims to examine the effect of enterprise risk management disclosure, intellectual capital disclosure and structure management on firm value. The population in this study are manufacturing companies listed on the Indonesia Stock Exchange in 2012 – 2016. The samples of this study are fifty-two companies listed in Indonesia Stock Exchange selected by using purposive sampling method. Data analysis method used is multiple regression model. Based on the hypothesis tested proves that the intellectual capital disclosure, board director have the positive significant effect on firm value, and board commissioner independent have the negative significant effect on firm value, meanwhile enterprise risk management disclosure and committe audit no effect on firm value Keywords : enterprise risk management disclosure, intellectual capital disclosure, management structure, firm value.